A switch from tenofovir to entecavir prior to hepatitis B treatment cessation is associated with a reduced risk of off‐therapy relapse: An observational study. Issue 11 (8th August 2022) - Peng, Chien‐Wei; Jeng, Wen‐Juei; Yang, Hwai‐I; Liu, Yen‐Chun; Chien, Rong‐Nan; Liaw, Yun‐Fan
Abstract: Background and Aim: In HBeAg negative chronic hepatitis B (CHB) patients, clinical relapse (CR) occurs more frequently, much earlier and often more severely after stopping tenofovir (TDF) and other nucleos(t)ide analogues (Nucs) than after stopping entecavir (ETV). It is unknown whether off‐Nuc hepatitis flare can be alleviated by switching from one Nuc to another. Methods: HBeAg‐negative CHB patients who had stopped Nuc according to the APASL stopping rule and had been followed‐up for > 48 weeks after Nuc cessation were recruited. Patients were classified as four groups: ETV monotherapy (mono‐ETV), TDF monotherapy (mono‐TDF), switched to ETV (switch‐ETV), and switched to TDF (switch‐TDF). Both switch groups had switched to the replacement Nuc > 12 weeks prior to end of therapy. Propensity score matching (PSM) was performed to minimize confounders among groups. Cox regression analysis was used to identify risks factors for off‐Nuc CR and flares. Results: A total of 1309 patients (1022 mono‐ETV, 219 mono‐TDF, 40 switch‐ETV and 28 switch‐TDF) were enrolled. The median time to CR was 39, 13, 38 and 14 weeks in mono‐ETV, mono‐TDF, switch‐ETV and switch‐TDF respectively ( P < 0.001). After PSM, the mono‐ETV (adjusted HR: 0.39, P < 0.001) and switch‐ETV patients (adjusted HR: 0.41, P = 0.003) had both significantly later occurrence and lower rates of CR and flare. Conclusion: In summary, the incidence and timing of CR was determined by ETV or TDF in the last 3 months prior to end of treatment. Patients treated with non‐ETV‐Nuc switched to ETV > 12 weeks before end of the original Nuc therapy may reduce/defer CR.